Museums and Geoconservation - Michael J. Benton; Sarah King (Geoconservation Research)
While museums have long been associated with the protection and interpretation of cultural, historical, and natural heritage, their role in geoconservation has only become more prominent in recent decades. Geoconservation focuses on the conservation of geological features, processes, and landscapes, and has gained recognition as an important area of environmental protection, particularly in the context of climate change and anthropogenic pressures on natural resources. Importantly, geoconservation is based on the fundamental scientific evaluation of those locations, such as open landscapes, coastlines, and quarries in terms of their regional and international significance.